New Insights Reached via Graded-Interfaces Modeling: How High-Power, High-Efficiency Mid-Infrared QCLs Work - Dan Botez; Suraj Suri; Huilong Gao; Thomas Grange; Jeremy D. Kirch; Luke J. Mawst; Robert A. Marsland (Photonics)
Graded-interfaces modeling unveils key features of high-power, high-efficiency quantum-cascade lasers (QCLs): direct resonant-tunneling injection from a prior-stage, low-energy state into the upper-laser (ul) level, over a wide (~50 nm) multiple-barrier region; and a new type of photon-induced carrier transport (PICT). Stage-level QCL operation primarily involves two steps: injection into the ul level and photon-assisted diagonal transition. Furthermore, under certain conditions, a prior-stage low-energy state, extending deep into the next stage, is the ul level, thus making such devices injectionless QCLs and leading to stronger PICT action due to quicker gain recovery. Thermalization within a miniband ensures population inversion between a state therein and a state in the next miniband. Using graded-interfaces modeling, step-tapered active-region (STA) QCLs possessing PICT action have been designed for carrier-leakage suppression. A preliminary 4.6 µm emitting STA design of a metal–organic chemical-vapor deposition (MOCVD)-grown QCL led to an experimental 19.1% front-facet, peak wall-plug efficiency (WPE). Pure, diffraction-limited beam operation is obtained at 1.3 W CW power. A low-leakage 4.7 µm emitting design provides a projected 24.5% WPE value, considering MOCVD-growth, graded-interface interface-roughness (IFR) parameters, and waveguide loss (αw). The normalized leakage-current density, Jleak/Jth, is 17.5% vs. 28% for the record-WPE 4.9 µm emitting QCL. Then, when considering the IFR parameters and αw values of optimized-crystal-growth QCLs, Jleak/Jth decreases to 13.5%, and the front-facet WPE value reaches 33%, thus approaching the ~41% fundamental limit. The potential of graded-interfaces modeling to become the design tool for achieving room-temperature operation of terahertz QCLs is discussed.